Cognitive Therapys from Rumi’s Point of View - Mehmet Ak; Elif Eþen; Faik Özdengül (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Psychotherapy is a general name of interventions used to resolve emotional conflicts, support and sustain the improvement of mental health. Relationship is one of the most important factors of regenerative effect in psychotherapy. Understanding the client is crucial to help the client understand the psychotherapy and psychotherapist. Thus, in order to be effective in psychotherapeutic interventions, it is neccessary to use the language by considering the client’s believes, culture, religion and background. Comprehending and using of psychotherapy only from the Western point of view could reduce the efficacy of psychotherapy. Although, it is common that people working in mental health area learn and use the techniques of authorities lived in West, our culture is considerably wealthy of thoughts and aspects that can be used in psychotherapy. Raised on the lands that have extremely rich cultural heritage, as psychotherapists, we think that it is our responsibility to integrate modern psychotherapy with cultural heritage when learning, practicing and teaching the practice of psychotherapy. In this article, it is aimed to increase the awareness of being able to use the philosophy of Mevlana Celaleddin Rumi whose masterpieces involve psychotherapeutic elements yet are not well understood and who has been an inspration to the trends in psychotherapy which are currently described as third generation trends. [JCBPR 2014; 3(3.000): 133-141]